The 2019 Revised Version of Association Research Circulation Osseous Staging System of Osteonecrosis of the Femoral Head - Yoon, Byung-Ho; Mont, Michael A.; Koo, Kyung-Hoi; Chen, Chung-Hwan; Cheng, Edward Y.; Cui, Quanjun; Drescher, Wolf; Gangji, Valerie; Goodman, Stuart B.; Ha, Yong-Chan; Hernigou, Philippe; Hungerford, Marc W.; et al. (The Journal of arthroplasty, 2020)
The Association Research Circulation Osseous (ARCO) presents the 2019 revised staging system of osteonecrosis of the femoral head (ONFH) based on the 1994 ARCO classification. In October 2018, ARCO established a task force to revise the staging system of ONFH. The task force involved 29 experts who used a web-based survey for international collaboration. Content validity ratios for each answer were calculated to identify the levels of agreement. For the rating queries, a consensus was defined when more than 70% of the panel members scored a 4 or 5 rating on a 5-point scale. Response rates were 93.1%-100%, and through the 4-round Delphi study, the 1994 ARCO classification for ONFH was successfully revised. The final consensus resulted in the following 4-staged system: stage I—X-ray is normal, but either magnetic resonance imaging or bone scan is positive; stage II—X-ray is abnormal (subtle signs of osteosclerosis, focal osteoporosis, or cystic change in the femoral head) but without any evidence of subchondral fracture, fracture in the necrotic portion, or flattening of the femoral head; stage III—fracture in the subchondral or necrotic zone as seen on X-ray or computed tomography scans. This stage is further divided into stage IIIA (early, femoral head depression ≤2 mm) and stage IIIB (late, femoral head depression >2 mm); and stage IV—X-ray evidence of osteoarthritis with accompanying joint space narrowing, acetabular changes, and/or joint destruction. This revised staging system does not incorporate the previous subclassification or quantitation parameters, but the panels agreed on the future development of a separate grading system for predicting disease progression. A staging system has been developed to revise the 1994 ARCO classification for ONFH by an expert panel-based Delphi survey. ARCO approved and recommends this revised system as a universal staging of ONFH.